Identity in Northeast Indian literature : Rereading select writings from Meghalaya - Lalkulhpuia, Dustin (London, UK: New York, USA: Routledge, 2025)
"This book provides an in-depth analysis and critical examination of the representation of ethnic, sexual, cultural and individual identities in selected literary works by contemporary writers from Northeast India. The book explores the complex dynamics of identity construction, sexuality, marginalization, ethnicity, and belonging in the context of Meghalaya and northeast India as a whole. The author analyses poetry and prose by Janice Pariat, Anjum Hasan, Kynpham Singh Nongkynrih and other Khasi writers. These works candidly portray the turmoil afflicting contemporary Meghalaya - from insurgency and ethnic tensions to ecological threats and loss of roots as well as reconciliation, integration and mutual understanding. Using postmodern and postcolonial literary strategies, the book depicts fluid, heterogeneous, and multifaceted notions of identity in Northeast India. An exploration of ethnicity, belonging, and unbelonging in the northeastern context, this book presents marginalized voices and liminal spaces. It will be of interest to academics focusing on Indian English literature, postcolonial literature and South Asian Studies"--
Rethinking identity in Northeast India: Contestations and negotiations -- Myth and identity: indigeneity and narrative agency -- Violence and identity: the politics of belonging and unbelonging -- Sexuality and identity: queering Pariat's fictional characters -- Conclusion.
Includes bibliographical references and index.
Keywords: Indic literature -- India, Northeastern -- History and criticism; Indic literature -- India -- Meghalaya; India, Northeastern -- In literature; India -- Meghalaya -- In literature; Identity (Psychology) in literature